Digital Leadership Influencing the Capabilities of Early Childhood Education Organizations in School Mover I Bandung - Mulyaniapi, Tepi; Permana, Johar; Soemarto, Soemarto; Nurdin, Diding (Mimbar Sekolah Dasar, 2024)
The study aims to investigate the challenges and issues arising from the impact of digital leadership and organizational capabilities on Early Childhood Education (ECE) School Mover in Bandung City. This includes understanding how these factors may hinder or enhance the educational environment in such institutions. This research examines the influence of digital leadership and organizational capabilities in Early Childhood Education (ECE) School Mover in Bandung City. The author used the Structure Equation Model (SEM) in conjunction with quantitative methods on a sample of 238 participants. Results indicate that all indicators on both variables effectively reflect the latent variables, and show a strong level of validity. These findings underscore the significance of digital leadership in enhancing educational organizational capabilities. Even though ECE is part of School Mover, with the vision "Freedom to Learn, Freedom to Play," this research reveals that there is still a gap between the need for digitalization in education and the ability of ECE organizations to adopt digital technology. Efforts to overcome this inequality must include technology training for teaching staff, support from the government, adequate budget allocation, and a leadership model that can lead ECE organizations in adopting digital technology. The demonstrated strong correlation between digital leadership and organizational capabilities underscores the need for targeted interventions to bridge the digital leadership implementation gap in ECE.